2020
DOI: 10.1016/j.amjoto.2020.102496
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and hearing difficulties

Abstract: The authors disclose no conflicts of interest. Journal Pre-proof J o u r n a l P r e -p r o o f have been proposed internationally so far (i.e. speech-to-text mobile apps, written scripts, masks with a plastic panel over the mouth) 9 , but their application in medical daily routine is still limited and has to be tested yet. In conclusion, further research to provide effective solutions and global strategies is needed. Journal Pre-proof J o u r n a l P r e -p r o o f 4 AKNOWLEDGEMENTS We would like to thank all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 5 publications
2
85
0
6
Order By: Relevance
“…A potential solution to this face covering problem is the use of transparent face coverings (Atcherson et al 2017). Trecca, Gelardi, and Cassano (2020) reported that more patients with hearing loss attributed problems with surgical masks to the inability to lip read than to muffled speech. This indicates that increasing visibility of the face to allow for speechreading and People are trying harder to be nicerit's one of the only positives!…”
Section: Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential solution to this face covering problem is the use of transparent face coverings (Atcherson et al 2017). Trecca, Gelardi, and Cassano (2020) reported that more patients with hearing loss attributed problems with surgical masks to the inability to lip read than to muffled speech. This indicates that increasing visibility of the face to allow for speechreading and People are trying harder to be nicerit's one of the only positives!…”
Section: Themesmentioning
confidence: 99%
“…Thus it is reasonable to expect that face coverings will impact those with hearing loss to a greater extent than those with normal hearing. Indeed patients with hearing loss seen in an Italian hospital during the COVID-19 pandemic reported significant communication difficulties, which were more often attributed to inability to lipread (56%) than to speech being muffled (44%) (Trecca, Gelardi, and Cassano 2020). Worries about face coverings were also reflected in a recent survey by Naylor, Burke, and Holman (2020).…”
Section: Introductionmentioning
confidence: 98%
“…The limited literature in this area has focused on face masks as a barrier to communication; early findings from an Italian hospital suggest that hearing-impaired patients had difficulty in understanding healthcare workers wearing face masks, due to muffled speech and impossibility of lipreading (Trecca et al 2020), while Chodosh et al (2020) provide an overview of the challenges people with hearing loss face from a clinical perspective as medical staff are required to wear face masks. To date at the time of writing, face masks have predominantly been worn by key workers such as medical professionals and shop assistants.…”
Section: Introductionmentioning
confidence: 99%
“…Auch wird der HNO-Arzt mit der Durchführung von nasalen Abstrichtests konfrontiert [18]. In den letzten Wochen wurden Berichte veröffentlicht, wonach gehäuft sensorineurale Hörstörungen bei COVID-19-Patienten oder diffuser Schwindel auftreten können, wobei die Hörstörung persistieren kann [14,[19][20][21]. Dieses überrascht bei der nachgewiesenen Neurotropie des Virus nicht [16,17].…”
Section: Vorbemerkungenunclassified